-2f-3=2f-25

Simple and best practice solution for -2f-3=2f-25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2f-3=2f-25 equation:



-2f-3=2f-25
We move all terms to the left:
-2f-3-(2f-25)=0
We get rid of parentheses
-2f-2f+25-3=0
We add all the numbers together, and all the variables
-4f+22=0
We move all terms containing f to the left, all other terms to the right
-4f=-22
f=-22/-4
f=5+1/2

You can always share this solution

See similar equations:

| 5-4x=23+2x | | 7+6e=4e-5 | | 7^x=3.5 | | 8x+22+9x+6=180 | | 12x-4=4(2x+2) | | 1.22x-9(3x-4)=1.29(x+5)-6 | | 1.09x-4(3x-9)=1.12(x+5)-2 | | 30/x-100=0 | | 5(3x-4)-1.10x=7-1.31(x+3) | | -3r-15=0 | | 5x-3(2/3x)=7 | | 11=y/2=9 | | 6x^2+5x+30=0 | | 14-v=236 | | 3x^2-5x+1=8x^2-2x-9 | | 0.3x^2+4x-3000=0 | | 48000=x+x*1/100 | | 48000=x+(x*1/100) | | Y=46-7x | | 17+p=17 | | 5.5x+14=36 | | 8w/4-9=2 | | x-0.35x=537 | | x*x-69x+1080=0 | | 4((2x-2)=6(3x+2) | | 4v^2+16v-48=0 | | -2x+3/2=x/4-12 | | x+6/4=x/4+6 | | (2x-1)=5(x+2) | | 67=n-84 |

Equations solver categories